Analisis Kesalahan Penggunaan Hyoogen “temo ii” Dalam Bahasa Jepang Pada Mahasiswa Upi Bandung - Juju Juangsih; Noviyanti Aneros (Bina Nusantara University, 2011)
This research will study the use of “temo ii” of 31 students seventh semester in UPI. This study uses analysis descriptive method by collecting data from students to take 20 questions. It can be concluded that the understanding of the use of “temo ii” of students show good scores about 53,39 % at average. There are three students who get 14 points (70%) which is the highest score. On the otherhand there is one student who gets 5 points (25%) which is the lowest score. Although the result shows they are above average, but some students still missuse the word “temo ii”. Moreover, they think the word “boleh” in Indonesia can be replaced by “temo ii”. However, the word “boleh” can not usualy be defined by “temo ii”.